Small airway function measured using forced expiratory flow between 25% and 75% of vital capacity and its relationship to airflow limitation in symptomatic ever-smokers: a cross-sectional study. Issue 1 (6th October 2022) - Alobaidi, Nowaf Y; Almeshari, Mohammed; Stockley, James; Stockley, Robert Andrew; Sapey, Elizabeth
Abstract : Background: Chronic obstructive pulmonary disease (COPD) is diagnosed and its severity graded by traditional spirometric parameters (forced expiratory volume in 1 s (FEV1 )/forced vital capacity (FVC) and FEV1, respectively) but these parameters are considered insensitive for identifying early pathology. Measures of small airway function, including forced expiratory flow between 25% and 75% of vital capacity (FEF25-75 ), may be more valuable in the earliest phases of COPD. This study aimed to determine the prevalence of low FEF25-75 in ever-smokers with and without airflow limitation (AL) and to determine whether FEF25-75 relates to AL severity. Method: A retrospective analysis of lung function data of 1458 ever-smokers suspected clinically of having COPD. Low FEF25-75 was defined by z-score<−0.8345 and AL was defined by FEV1 /FVC z-scores<−1.645. The severity of AL was evaluated using FEV1 z-scores. Participants were placed into three groups: normal FEF25-75 / no AL (normal FEF25-75 /AL−); low FEF25-75 / no AL (low FEF25-75 /AL−) and low FEF25-75 / AL (low FEF25-75 /AL+). Results: Low FEF25-75 was present in 99.9% of patients with AL, and 50% of those without AL. Patients in the low FEF25-75 /AL− group had lower spirometric measures (including FEV1 FEF25-75 /FVC and FEV3 /FVC) than those in the normal FEF25-75 /AL− group. FEF25-75 decreased with AL severity. A logistic regression model demonstrated that in the absence of AL, the presence of low FEF25-75 was associated with lower FEV1 and FEV1 /FVC even when smoking history was accounted for. Conclusions: Low FEF25-75 is a physiological trait in patients with conventional spirometric AL and likely reflects early evidence of impairment in the small airways when spirometry is within the 'normal range'. FEF25-75 likely identifies a group of patients with early evidence of pathological lung damage who warrant careful monitoring and reinforced early intervention to abrogate further lung injury.